Artificial Intelligence in Medical Image Processing and Segmentation - Zaffino, Paolo; Spadea, Maria Francesca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint showcases a selection of bleeding-edge articles about medical image processing and segmentation workflows based on artificial intelligence algorithms. The proposed papers are applied to multiple and different anatomical districts and clinical scenarios.